Perlindungan Hukum terhadap Keluarga Justice Collaborator - Sri Wardani Sirait; Nisa Permata Sari; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The purpose of writing this article is to identify and analyze how legal protection and rights are regulated for families with Justice Collaborator status in an effort to uncover criminal acts. The method in this study uses a normative juridical approach. From the research conducted, the authors obtained results in the form of legal protection for Justice Collaborator families who have protection and have rights including supervision and escort, provision of body security equipment, provision of medical and psychological services, reimbursement of living expenses during the protection period, reimbursement of accommodation costs and transportation during the protection period, protection provided in a safe house, relocation and a new identity in accordance with Undang Undang No 31 Tahun 2014 Pasal 5 concerning the protection of witnesses and victims. Keywords: legal protection, justice collaborator, crime.